1993
DOI: 10.1007/bf00180468
|View full text |Cite
|
Sign up to set email alerts
|

Extended structural defects in ?-Hgl2 single crystals

Abstract: Extended structural defects in both ~-Hgl 2 crystals grown in solution or from the vapourphase were studied by optical microscopy, light scattering, SEM operated in cathodoluminescence and in secondary electron mode, X-ray topography, neutron, y-and X-ray rocking curves and oscillating crystal X-ray diffraction. The observed dislocations were compared with theoretically calculated dislocations. Dislocation loops, having diameters ranging from 2 gm to 500 gm, are observed on all low index faces, Hohlstellen (le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 162 publications
(200 reference statements)
1
4
0
Order By: Relevance
“…From the length-to-depth aspect ratio of the defects, it is apparent that on average, the defects tend to extend to a greater degree within the (001) plane making up the layers. Micrograph (D) presents a wide area view from the ingot center showcasing the finding that defects within the bulk tend to take on trigonal form, some of which are strikingly similar to the void inclusions presented by Nicolau et al in α-HgI 2[15].Further evidence that these defects are indeed voids (sometimes called negative crystals in literature) and not inclusions came from bisecting the defects by cleaving sections of the crystal in half. Use of optical micrographs focused on the both surfaces of the isolated defects revealed no inclusions or secondary phases in either half of the sample.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…From the length-to-depth aspect ratio of the defects, it is apparent that on average, the defects tend to extend to a greater degree within the (001) plane making up the layers. Micrograph (D) presents a wide area view from the ingot center showcasing the finding that defects within the bulk tend to take on trigonal form, some of which are strikingly similar to the void inclusions presented by Nicolau et al in α-HgI 2[15].Further evidence that these defects are indeed voids (sometimes called negative crystals in literature) and not inclusions came from bisecting the defects by cleaving sections of the crystal in half. Use of optical micrographs focused on the both surfaces of the isolated defects revealed no inclusions or secondary phases in either half of the sample.…”
supporting
confidence: 56%
“…Spectral responses from alpha particles [8,10,12] and, more recently, low-energy gamma rays [13], have been demonstrated in this material. However, stacking fault-related defects observed in other layered-structure semiconductors [14][15][16] present a cause for concern in fabricating spectral quality Sb:BiI 3 detectors. High-grade crystals are necessary to collect well-resolved gamma-ray spectra for most nuclear security and medical radiology applications.…”
Section: Introductionmentioning
confidence: 99%
“…There are various types of defects, in which the spiral (screw) defects are also very common in the process of fabricating microstructures. The characteristics of these defects have been described in refs 43 and 44 . In the following, we discuss how to identify the spiral defects by using these states.…”
Section: Resultsmentioning
confidence: 99%
“…Milstein et al 1 conducted optical microscopy studies of mercuric iodide which, by selective etching, revealed dislocations and low angle boundaries that originated from microhardness measurements. 3 However, an important impediment to studying ␣-HgI 2 , PbI 2 , and BiI 3 surfaces with higher-resolution techniques ͑which require vacuum conditions͒, such as transmission electron microscopy ͑TEM͒ and scanning electron microscopy ͑SEM͒, has been the high vapor pressure of these compounds at ambient temperature. 2 The effects of dopants on the crystal microstructure and the segregation of impurities during the growth process were reported.…”
Section: Introductionmentioning
confidence: 99%